Management of the Unexpected Difficult Airway in Neonatal Resuscitation - Berisha, Gazmend; Boldingh, Anne Marthe; Blakstad, Elin Wahl; Rønnestad, Arild Erlend; Solevåg, Anne Lee (Frontiers in Pediatrics, 2021)
A ‘difficult airway situation’ arises whenever face mask ventilation, laryngoscopy, endotracheal intubation, or use of supraglottic device fail to secure ventilation. As bradycardia and cardiac arrest in the neonate are usually of respiratory origin, neonatal airway management remains a critical factor. Despite this, a well-defined in-house approach to the neonatal difficult airway is often lacking. While a recent guideline from the British Paediatric Society exists, and the Scottish NHS and Advanced Resuscitation of the Newborn Infant (ARNI) airway management algorithm was recently revised, there is no Norwegian national guideline for managing the unanticipated difficult airway in the delivery room (DR) and neonatal intensive care unit (NICU). Experience from anesthesiology is that a ‘difficult airway algorithm’, advance planning and routine practicing, prepare the resuscitation team to respond adequately to the technical and non-technical stress of a difficult airway situation. We learned from observing current approaches to advanced airway management in DR resuscitations in a university hospital and make recommendations on how the neonatal difficult airway may be managed through technical and non-technical approaches. Our recommendations mainly pertain to DR resuscitations but may be transferred to the NICU environment.